Haematological profile of healthy pregnant women in Ibadan, South-western Nigeria (2006)
There is a dearth of information on the reference values for haematological indices particularly according to the relevant trimesters of pregnant women in Nigeria. The objective of this study was to provide reference values for Nigerian pregnant women. The study took place at the Adeoyo Maternity Hospital and the University College Hospital, both in Ibadan. This descriptive study was carried out over a period of 8 months. Subjects were apparently healthy pregnant women that satisfied the inclusion and exclusion criteria. The mean values (and 95% confidence intervals, CI) of haematological indices were as follows -- First trimester: Haemoglobin (Hb) 112.44 (101.64 - 123.25) g/l, haematocrit (hct) 35 (32 - 38)%, WBC 5.488 (4.025 - 6.950) x 10(9)/l and platelet counts 227.56 (165.21 - 289.90) x 10(9)/l;Second trimester: Hb 100.39 (97.85 - 102.92) g/l, hct 29.3 (28.5 - 30.1)%, WBC 6.57 (6.19 - 6.95) x 10(9)/l, platelet count 229.56 (211.86 - 247.26); and the Third trimester: Hb 98.06 (96.12 - 100.00) g/l, hct 29.4 (28.7 - 29.9)%, WBC 6.92 (6.53 - 7.30), platelet count 186.52 (177.67 - 195.38) x 10(9)/l. These results were compared with those of 52 non-pregnant age matched women volunteers as controls whose mean haematological indices and 95% CI were: Hb 120.51 (116.61 - 124.41) g/l, hct 36 (25 - 48)%, WBC 5.28 (2.9 - 8.7) x 10(9), platelet count 330.87 (176 - 538) x 10(9)/l. The following haematological indices: WBC, platelet counts, RBC, PCT, and PDW, of women between the trimesters showed statistical significance (p value < 0.001 in each case). The WBC is inversely proportional to the PCT and the MCV in the pregnant women was slightly raised. In this study, pregnancy is characterised by lowest values of haemoglobin parameters in trimester three and there are statistically significant differences between the WBC, platelet counts, RBC, PCT, and PDW of women between the three trimesters.